Efficacy of bioflavonoid quercetin in treatment of herpetic keratitis patients with dry eye syndrome (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Dry eye syndrome has drown a  special attention of ophthalmologists not only because of its prevalence but also due to the increased frequency among patients with inflammatory processes in the cornea and conjunctiva.Purpose. To study the effect of bioflavonoid quercetin on the course of the inflammatory process in patients with herpetic keratitis (HK) and dry eye syndrome (DES).  Material and Methods. Clinical study involved 40 patients (40 eyes) with HK (superficial keratitis) and DES; in addition, we followed up 17 patients (17 eyes) with HK-only. All patients involved in the clinical study were divided into two groups: Study Group, HK and DES patients receiving bioflavonoid quercetin, containing in Lipoflavon drug, in addition to traditional treatment, 15 patients; Control Group, HK and DES patients receiving only traditional treatment, 25 patients. Results. Clinical study findings showed that the inclusion of bioflavonoid quercetin (Lipoflavon) in the complex treatment of HK patients with DES significantly decreased the intensity of clinical signs and made it possible to decrease the treatment duration. Corneal dendritic ulceration epithelization was observed significantly earlier in patients with HK and SED receiving Lipoflafon as compared to controls, at Day (4.7±0.4) vs. Day (6.8±0.6), respectively; no corneal infiltration was observed at Days (5.5±0.5) and (7.8±0.7) in Study and Control groups, respectively. Schirmer test II values were (10.47±0.83) mm/5 min and (7.36±0.28) mm/5 min in Study and Control groups, respectively. Tear break-up time equaled (6.13±0.32) and (5.24±0.19) s, in Study and Control groups, respectively.Conclusions. Inclusion of bioflavonoid quercetin in the complex treatment of patients with herpetic keratitis and dry eye syndrome significantly increases the therapy efficacy, which is evidenced by accelerated corneal epithelization and infiltrate dispersion and significantly improved qualitative and quantitative characteristics of tear production.
Keywords: herpetic keratitis; dry eye syndrome; Lipoflavon